Modified docetaxel, cisplatin and fluorouracil therapy as the first-line treatment for patients with recurrent/metastatic squamous cell carcinoma of the head and neck cancer: a retrospective study - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Aim: Modified docetaxel, cisplatin, and 5-fluorouracil (mDCF) therapy has been shown to be a well tolerated and highly effective regimen for metastatic gastric carcinoma. Herein we investigated the effectiveness of the mDCF combination as the first-line treatment in patients with recurrent/metastatic squamous cell carcinoma of the head and neck (HNSCC). Methods: A total of 80 patients with recurrent/metastatic HNSCC who were treated with mDCF between 2009 and 2015 were enrolled into this study. All patients were treated in the first-line with 2-6 cycles of mDCF chemotherapy which consisted of docetaxel 60 mg/m(2) intravenously (IV) on day 1, cisplatin 60 mg/m(2) IV on day 1, and 5-fluorouracil 600 mg/m(2) IV for 5 days of continuous infusion, with cycles repeated every 21 days. Results: The most common grade 3-4 toxicities were neutropenia (22.5%), anemia (10%), thrombocytopenia (7.5%), nephrotoxicity (1.3%), hepatotoxicity (1.3%), and diarrhea (2.5%). Twelve patients (15%) experienced a febrile neutropenic episode. Dose modification was required in 22 (27.5%) of the patients due to drug toxicity. Complete response was achieved in 2.5% of all patients, while partial and stable responses were reported to be 43.8% and 25%, respectively, with a disease control rate of 71.3%. The median progression-free and overall survival was 7 (95% CI: 5.3-8.6) and 11.5 (95% CI: 9.4-13.7) months, respectively. Conclusions: The efficiency of the mDCF combination for induction chemotherapy has been well established previously. To our knowledge, this is one of the largest studies evaluating the survival and safety significance of mDCF chemotherapy as a first-line treatment in patients with recurrent/metastatic HNSCC.
Keywords: Cisplatin; docetaxel; fluorouracil; head and neck; cancer; metastasis; modified DCF; recurrence; COOPERATIVE-ONCOLOGY-GROUP; MULTICENTER PHASE-II; METASTATIC HEAD; PLUS CETUXIMAB; RANDOMIZED-TRIAL; OPEN-LABEL; RECURRENT; CHEMOTHERAPY; 5-FLUOROURACIL; METHOTREXATE